2014
DOI: 10.1002/marc.201400627
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Investigation of Midblock‐Sulfonated Block Ionomers Prepared from Solvents Differing in Polarity

Abstract: Recent developments regarding charged multiblock copolymers that can form physical networks and exhibit robust mechanical properties herald new and exciting opportunities for contemporary technologies requiring amphiphilic attributes. Due to the presence of strong interactions, however, control over the phase behavior of such materials remains challenging, especially since their morphologies can be solvent-templated. In this study, transmission electron microscopy and microtomography are employed to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
67
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 56 publications
7
67
0
Order By: Relevance
“…Moreover, the performance of OPVs can be improved through the physical incorporation of conductive nanoscale objects (e.g., carbon nanotubes) to produce hybrid materials. Since the morphologies of block ionomers can be solvent-templated [ 34 ] and to ensure that the ionic pathway in these SBIs is continuous, fi lms have been cast from a polar organic solvent. Another class of promising and inexpensive OPVs that have received substantial attention since the seminal work of Grätzel and co-workers [ 16,17 ] includes dye-sensitized solar cells (DSSCs).…”
Section: Doi: 101002/aenm201401941mentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the performance of OPVs can be improved through the physical incorporation of conductive nanoscale objects (e.g., carbon nanotubes) to produce hybrid materials. Since the morphologies of block ionomers can be solvent-templated [ 34 ] and to ensure that the ionic pathway in these SBIs is continuous, fi lms have been cast from a polar organic solvent. Another class of promising and inexpensive OPVs that have received substantial attention since the seminal work of Grätzel and co-workers [ 16,17 ] includes dye-sensitized solar cells (DSSCs).…”
Section: Doi: 101002/aenm201401941mentioning
confidence: 99%
“…This observation verifi es that Ru(bpy) 3 complexes with the polymer in the presence of water. [ 34 ] These channels, measuring 12-14 nm across, are the result of using a polar casting solvent. This difference is accompanied by the development of a second peak located at 1040 cm −1 and similarly suggests that Ru(bpy) 3 complexes with both the polymer and DAS.…”
Section: Doi: 101002/aenm201401941mentioning
confidence: 99%
See 2 more Smart Citations
“…Such favorable agreement implies that, despite being (i) constrained between lamellae (which behave as soft parallel surfaces [34]), (ii) tethered at one chain end, and (iii) surrounded by double-anchored midblocks, the interstitial micelles reported in this study form as if they were free micelles in the bulk. While bicomponent ABA triblock copolymers normally order into single morphologies, numerous experimental stud ies [35,36] have demonstrated that coexisting morphologies frequently develop during solvent casting. Recent evidence [37] acquired from melt-spun bicomponent fibers confirms that dual-mode nanostructures (e.g., tubes containing centerline micelles) can likewise form in solvent-free systems.…”
mentioning
confidence: 99%